Incentives in Discrete-Time MDP Processes with Flexible Step-Size - Green, Jerry; Schoumaker, Francoise (Review of Economic Studies, 1980)
Jerry Green, Françoise Schoumaker; Incentives in Discrete-time MDP Processes with Flexible Step-size, The Review of Economic Studies, Volume 47, Issue 3, 1 Apri